+0

# Relationship between n*ϕ and ϕ^n

0
238
3

What is the relationship of nϕ and ϕ^n, when n=1, 2, 3, 4, ..., 15

Guest Aug 22, 2017
Sort:

#1
+19207
0

Relationship between n*ϕ and ϕ^n

What is the relationship of nϕ and ϕ^n, when n=1, 2, 3, 4, ..., 15

Formula:
$$\begin{array}{rcll} \phi^n &=& F_{n}\phi +F_{n-1}\\ F_{n-2} &=& F_{n}-F_{n-1}\\ \frac{1}{\phi} &=& \phi -1 \\ \end{array}$$

List of Fibonacci numbers:

$$\small{ \begin{array}{|c|c|c|c|c|c|c|c|c|c|c|c|c|c|c|c|c|c|} \hline F_{-2} & F_{-1} & F_0 & F_1 & F_2 & F_3 & F_4 & F_5 & F_6 & F_7 & F_8 &F_9 &F_{10} &F_{11} &F_{12} &F_{13} &F_{14} &F_{15} \\ \hline -1 & 1 & 0 & 1 & 1 & 2 & 3 & 5 & 8 & 13 & 21 & 34 & 55 & 89 & 144 & 233 & 377 & 610 \\ \hline \end{array} }$$

$$\begin{array}{|rcll|} \hline \text{relationship } &=& \frac{n\phi}{\phi^n} \\ &=& \frac{n\phi}{F_{n}\phi +F_{n-1}} \\ &=& \frac{n}{ \frac{F_{n}\phi +F_{n-1} } {\phi} } \\ &=& \frac{n}{ F_{n} + \frac{1}{\phi} F_{n-1} } \\ &=& \frac{n}{ F_{n} + (\phi -1) F_{n-1} } \\ &=& \frac{n}{ F_{n} + F_{n-1}\phi -F_{n-1} } \\ &=& \frac{n}{ F_{n}-F_{n-1} + F_{n-1}\phi } \\ &\mathbf{=}& \mathbf{\frac{n}{ F_{n-2} + F_{n-1}\phi }} \\ \hline \end{array}$$

$$\begin{array}{|r|l|} \hline \mathbf{n} & \mathbf{\frac{n\phi}{\phi^n} = \frac{n}{ F_{n-2} + F_{n-1}\phi }} \\ \hline 1 & \frac{ 1 }{ 1+0\phi } = 1 \\ 2 & \frac{ 2 }{ 0+1\phi } = \frac{2}{\phi}= 2(\phi -1) \\ 3 & \frac{ 3 }{ 1+1\phi } \\ 4 & \frac{ 4 }{ 1+2\phi } \\ 5 & \frac{ 5 }{ 2+3\phi } \\ 6 & \frac{ 6 }{ 3+5\phi } \\ 7 & \frac{ 7 }{ 5+8\phi } \\ 8 & \frac{ 8 }{ 8+13\phi } \\ 9 & \frac{ 9 }{ 13+21\phi } \\ 10 & \frac{10 }{ 21+34\phi } \\ 11 & \frac{11 }{ 34+55\phi } \\ 12 & \frac{12 }{ 55+89\phi } \\ 13 & \frac{13 }{ 89+144\phi } \\ 14 & \frac{14 }{ 144+233\phi } \\ 15 & \frac{15 }{ 233+377\phi } \\ \hline \end{array}$$

heureka  Aug 22, 2017
#2
0

Heureka, how did you get that ϕ^n=Fnϕ+Fn-1?

Guest Aug 23, 2017
#3
+19207
0

Heureka, how did you get that ϕ^n=Fnϕ+Fn-1 ?

Formula:  $$\phi^2 = \phi +1$$

mathematical proof:

$$\begin{array}{|rcll|} \hline \phi = \frac{1+\sqrt{5}} {2} \\\\ \phi^2 &=& \left( \frac{1+\sqrt{5}} {2} \right)^2 \\ &=& \frac{\left( 1+\sqrt{5}\right)^2 } {4} \\ &=& \frac{ 1+2\sqrt{5}+5 } {4} \\ &=& \frac{ 6+2\sqrt{5} } {4} \\ &=& \frac{ 3+\sqrt{5} } {2} \\ &=& \frac{ 1+2+\sqrt{5} } {2} \\ &=& \frac{ 1+\sqrt{5}+2 } {2} \\ &=& \frac{ 1+\sqrt{5} } {2} +\frac{2}{2} \\ &=& \frac{ 1+\sqrt{5} } {2} + 1 \\ &=& \mathbf{ \phi + 1 } \\ \hline \end{array}$$

$$\small{ \begin{array}{|lclclclcl|} \hline \phi^1&&&& &=& 1\phi+0 &=& F_1\phi + F_0 \\ \phi^2&&&& &=& 1\phi+1 &=& F_2\phi + F_1 \\ \phi^3 = \phi\phi^2 = \phi(\phi+1) &=&1\phi^2 + 1\phi &=&1(\phi+1)+1\phi &=& 2\phi+1 &=& F_3\phi + F_2 \\ \phi^4 = \phi\phi^3 = \phi(2\phi+1) &=&2\phi^2 + 1\phi &=&2(\phi+1)+1\phi &=& 3\phi+2 &=& F_4\phi + F_3 \\ \phi^5 = \phi\phi^4 = \phi(3\phi+2) &=&3\phi^2 + 2\phi &=&3(\phi+1)+2\phi &=& 5\phi+3 &=& F_5\phi + F_4 \\ \phi^6 = \phi\phi^5 = \phi(5\phi+3) &=&5\phi^2 + 3\phi &=&5(\phi+1)+3\phi &=& 8\phi+5 &=& F_6\phi + F_5 \\ \phi^7 = \phi\phi^6 = \phi(8\phi+5) &=&8\phi^2 + 5\phi &=&8(\phi+1)+5\phi &=& 13\phi+8 &=& F_7\phi + F_6 \\ \phi^8 = \phi\phi^7 = \phi(13\phi+8) &=&13\phi^2 + 8\phi &=&13(\phi+1)+8\phi &=& 21\phi+13 &=& F_8\phi + F_7 \\ \phi^9 = \phi\phi^8 = \phi(21\phi+13) &=&21\phi^2 + 13\phi &=&21(\phi+1)+13\phi &=& 34\phi+21 &=& F_9\phi + F_8 \\ \phi^{10} = \phi\phi^9 = \phi(34\phi+21) &=&34\phi^2 + 21\phi &=&34(\phi+1)+21\phi &=& 55\phi+34 &=& F_{10}\phi + F_9 \\ \cdots \\ \mathbf{ \phi^n } &&&& && &\mathbf{ =}& \mathbf{ F_n\phi + F_{n-1}} \\ \hline \end{array} }$$

heureka  Aug 23, 2017

### 46 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details